The Church in Mission in the Light of Ecclesia in Africa : a trilogy ; the church as the family of God building unity together in the mission of the church missionary ecclesiology - Onwubiko, Oliver Alozie (Gujarat : Gujarat Sahitya Prakash, 2002)
Contributed seminar papers.
Includes bibliographical references (p.467-472)
Keywords: Mission of the church -- Africa -- Congresses; Christianity -- Africa